A construção do mito Sergio Moro em Veja e CartaCapital: o herói e o justiceiro no jornalismo de revista - Evangelista, Vitor Carletti (2023)
An analysis of the construction of two antagonistic representations of Sergio Moro as a judge of Lava Jato, the largest lawfare operation ever carried out in Brazil in magazine journalism. The objective was to establish the characteristics of the formation of mythical narratives from six reports from Veja and four from CartaCapital that exposed the representation of Moro on their covers between the years 2014 to 2018. It was identified that magazine journalism builds ideological myths . To arrive at this definition, a study of the myths was carried out in order to identify the characteristics that form these media phenomena present in the studied publications. In addition, we sought to relate this study to the fundamentals of magazine journalism and reporting developed by Brazilian and international authors and researchers. The research sought to identify the intersection between the two types of narrative in order to confirm the hypothesis that the magazines each built a mythical representation of Moro as a Lava Jato judge. Veja represented Moro as a national hero, while in CartaCapital he was a vigilante. The analysis was based on the discursive construction of the covers, titles, fine lines and excerpts of the reports. The study reached the following conclusions: the myths produced by journalism are primarily the result of the ideology of the company responsible for the publication. The repetition of a unit of meaning, the systematic use of archetypal images linked to a stereotype present in society, the choice to defend a truth of opinion and the conflict narrative were elements highlighted during the work. The research deepened the theme in interviews with journalists who composed the teams of the magazines responsible for the editions. The analyzed data and the answered questions allowed the present study to establish and explain the narrative structure of magazine journalism that mythified, according to the ideology of each magazine, the representation of Sergio Moro as a Lava Jato judge.